Pengembangan Sistem Informasi E-Learning Peserta Magang Berbasis Web Pada BBPOM PALANGKARAYA Menggunakan Model Agile - Arotsid, Muhammad Farhan; Adriano, Riedo; Yusnadi, Muhammad Rizki; Haryono, Wasis (Jurusan Informatika STTR Cepu, 2025)
The Palangkaraya Center for Drug and Food Control (BBPOM) is facing challenges due to the increasing number of internship participants, which has caused difficulties in managing activities manually—from learning, monitoring activities, to evaluation. The conventional system is considered ineffective and unable to provide structured and real-time learning support. Therefore, it is necessary to develop a system that facilitates online learning and supports the entire internship process digitally.This study aims to design and develop an e-learning information system that can support a more efficient and digital internship process. The system design is carried out using the Unified Modeling Language (UML) to visually describe the structure and flow of the system. The system development adopts the Agile model, allowing iterative and flexible development according to user needs. With this system, the internship process is expected to become more organized, communication between supervisors and participants more effective, and the evaluation of internship outcomes more systematic and well-documented.